THE CONCEPT OF THE SHADOW ECONOMY AND SOME RECOMMENDATIONS FOR ITS ELIMINATION - Mamaonus Karshibayevich Pardaev; Najmiddin Rakhmatullaevich Abduvohidov (Web of Journals Publishing, 2025)
In this article, the authors theoretically justify the term “shadow (fake) economy,” which is considered a form of the hidden economy in the official sector, and systematize its manifestations. Attention is also paid to the economic consequences of the shadow economy. The authors have developed their own scientific proposals and conclusions on preventing and eliminating the shadow economy.
Keywords: Official sector, hidden economy, shadow (fake) economy, digital economy, informal employment, self-employment, unrecorded economic activity, taxable and non-taxable shadow economy.